Development of the Iconography of the Mesmeric Seance in French Art of the Late 19th Century - Martynova, Daria O. (Actual Problems of Theory and History of Art, 2023)
At the end of the 19th century, a large number of critical and theoretical texts on art appeared in France, which were based on the paranientific theory of mesmerism: for example, in the journal ’New Iconography of Salpetriere’ dedicated to the representations of pathologies in art, a group of physicians wrote a series of art criticism articles on engravings with mesmeric session. In a theoretical paper on hysteria, Paul Richer and Henri Meige formulated the idea of a proforma that anticipated Aby Warburg’s “pathos formula”. Doctors believed that certain visual images migrate in the history of art and become “emphatic”. As a result of these publications, the visualization of pathologies entered and found its place in the art of the second half of the 19th century. The symptom turned into a sign that needs to be read; thereby, the visual became the main thing in interpretation, which allowed us to bring gestures and poses from the field of fine art into the spatial: emphatic gestures formed protoperformative practices played out in the theater, cabaret, and café-concerts. The topic opens up the prospects for the analysis and revision of a number of themes and images in art and culture, whether it would be a trickster hypnotist or a magician and hypnotic sessions.This research has been completed with the support of the Russian Science Foundation (RSF), project no. 23-28-01577.
Keywords: French art; mesmerism; Jean-Martin Charcot; Aby Warburg; principle of visual analogy